Calcareous nannofossils across the Eocene-Oligocene transition at Site 756 (Ninetyeast Ridge, Indian Ocean): implications for biostratigraphy and paleoceanographic clues - Viganò A.; Coxall H. K.; Holmstrom M.; Vinco M.; Lear C. H.; Agnini C. (Newsletters on Stratigraphy, 2023)
The timing and modalities of calcareous phytoplankton community and evolutionary responses to the Eocene-Oligocene transition (EOT, ~34 Ma) are still under-investigated. In order to better constrain the dynamics of these pelagic primary producers during the climate transition, we conducted high resolution assemblage analysis on calcareous nannofossils across a ~19 m-thick interval of nannofossil ooze at Ocean Drilling Program (ODP) Site 756 (Ninetyeast Ridge, Indian Ocean; Peirce et al. 1989) (paleolatitude ~43° S; Zachos et al. 1992). We explored the diversity patterns against a new integrated planktonic foraminifera and calcareous nannofossil biostratigraphy produced for the site, as well as new benthic foraminifera and bulk sediment stable isotope (C, O) records, which documents ocean-climate changes, and provides independent chemostratigraphy. The study section spans nannofossil Zones NP20-NP23 (equivalent to CNE20-CNO4) and lasts 5.5 Myr. The results show that the hankeninid extinction falls within the ~4.5 m-thick EOT isotopic interval (0.67 m below the base of the second positive δ18 O shift – EOIS), which is consistent with previous studies, making Hole 756C one of a few sites globally boasting both the familiar stepped δ18 O and δ13 C structure of the EOT and the primary biostratigraphic marker defining the base of the Oligocene. A series of potentially useful new calcareous nannofossil bioevents were identified that could help improve dating and correlation of this crucial interval. In this context, changes in calcareous nannofossil assemblages observed across EOT are interpreted in terms of modifications of paleoecological parameters that typically control the abundance and distribution of different taxa. Variations in sea surface temperature and nutrient availability are considered to be the most likely triggers for the calcareous phytoplankton changes observed across EOT. Specifically, our data suggest that increased nutrients in the mixed layer played a key role in shaping the late Eocene – early ...